2023
DOI: 10.3390/ma16072675
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Cast Al-Si-Cu-Mg-Ni-Cr Alloys: Effects of Time and Temperature on Two-Stage Solution Treatment and Ageing

Abstract: Ameliorating the high-temperature performance of cast Al-Si alloys used as engine components is essential. The effects of different T6 heat-treatment processes on the microstructure and mechanical properties of cast Al-Si-Cu-Mg-Ni-Cr alloys were investigated in the present study. The results demonstrate that, under the optimal solution treatment conditions of 500 °C for 2 h and 540 °C for 4 h, the T-Al9FeNi phase was present in the alloy, and the roundness of primary Si and the aspect ratio of eutectic Si in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Thus, the modified alloys, especially, the B390-P-Bi alloy presenting many finer dimples, were observed on the fracture surfaces. Vuksanovic et al (2021) [51] and Xiao et al (2023) [52] indicated that dimples on fracture surfaces were present after the T6 heat treatment and they were significant on the surfaces of the Al-12.5Si alloy and Al-Si-Cu-Mg-Ni-Cr. Due to the rounding and coarsening of eutectic silicon phase, there was increased resistance to fracture.…”
Section: Fracture Surfacesmentioning
confidence: 99%
“…Thus, the modified alloys, especially, the B390-P-Bi alloy presenting many finer dimples, were observed on the fracture surfaces. Vuksanovic et al (2021) [51] and Xiao et al (2023) [52] indicated that dimples on fracture surfaces were present after the T6 heat treatment and they were significant on the surfaces of the Al-12.5Si alloy and Al-Si-Cu-Mg-Ni-Cr. Due to the rounding and coarsening of eutectic silicon phase, there was increased resistance to fracture.…”
Section: Fracture Surfacesmentioning
confidence: 99%
“…The Q phase is a key phase in Al alloys, including not only 6xxx series Cu-added Al-Mg-Si alloys [ 7 ], but also 4xxx series Cu-added Al-Si-Mg alloys [ 8 , 9 ] and 2xxx series Si-added Al-Cu-Mg alloys [ 10 ], existing as as-cast constituents [ 8 , 10 ] and nano-precipitates [ 9 , 11 ]. Abundant research has been conducted to clarify the precipitation behaviors of Al-Mg-Si(-Cu) alloys during age hardening, especially paint bake hardening, a typical heat treatment process for auto body panels [ 5 ], thus guiding the design of new generations of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Flemings, is an advanced forming process [ 7 , 8 ]. Compared with the hot die forging process, the forming force for the SSMF process is significantly decreased, due to the low flow stress and the good filling characteristic of the semi-solid metals, and the mechanical properties of the formed parts are close to those of the materials under the hot die forging condition [ 9 , 10 , 11 ]. As one of the SSFM processes, the semi-solid thixotropic forging forming (SSTFF) process, including the preparation of ideal semi-solid billets and the forging forming of components, has received extensive attention in recent years.…”
Section: Introductionmentioning
confidence: 99%